LEGAL STANDING PEMANTAU PEMILU SEBAGAI PEMOHON SENGKETA HASIL PEMILIHAN KEPALA DAERAH DENGAN CALON TUNGGAL - Arwi Aqif; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Legal standing is a prerequisite for filing perselisian material in the local election results to the Supreme Komstitusi. Implementation of the elections with a single candidate in 2015 the Constitutional Court has given a chance on election monitoring as a legal subject or the applicant in the dispute in the elections. The purpose of this thesis, namely; First, to know how the legal standing of election observers in election disputes with a single candidate, Secondly, to know how is the concept of dispute resolution with a single candidate election.This type of research is classified study of normative law this study further discusses the legal synchronization. The source of data is secondary data which is divided into 3 (three), which is the primary legal materials, secondary and tertiary. In the data collection methods of documentary study literature or studies. Data were analyzed quantitatively, the descriptive outline of the data obtained.From the research, there are two main things that can be inferred. Firstly, the Constitutional Court provides the opportunity for election monitoring as a legal subject / applicant in the dispute to the constitutional court which were previously not regulated in the Law on the Constitutional Court. Regarding the election observers as an applicant to the Constitutional Court that has been set in the PMK 4 in 2015 is contrary to the Law on Constitutional Court No. 25 Year 2003. Two, dispute resolution of disputes with a single candidate as well as the settlement of disputes in general. single candidate election implementation and completion of the election with a single candidate does not fit in the concept of democracy in their preferred electoral system more than one pair of candidates. Elections without konstestasi pemulu essentially not ideal in a democracy. The Constitutional Court is expected to issue a sage in any existing regulations, and the Government of the House of Representatives is expected to revise the Law on the Constitutional Court Number 24 of 2003 to enable the synchronization with existing regulations.Keywords: Legal Standing - Dispute Court.